DEVELOPMENT OF MACRO-BASED STRATEGIC PLANNING APPLICATION EXCEL: AS A TOOL FOR FORMULATING HUMAN RESOURCE MANAGEMENT SRATEGIS - Elfia Nora; Madziatul Churiyah (International Journal of Economics and Management Research, 2023)
Abstract So far, in formulating strategies in an organization, especially reviewing from the aspect of human resource management, analytical tools that are often used to process the data obtained are SWOT Analysts, Internal Factor Analysis and External factors and Competitive Profile Matrix how to analyze the strength of weaknesses in opportunities and threats of a company (SWOT) and matrix Competitive profile analyzes the strategic position of the company compared to similar competitors, especially in terms of human resource management, namely employees, because employees are the spearhead of an organization. The purpose of software development in the form of this application is so that it can be used to formulate strategies in the organization and its specifics can be applied also to formulate strategies in the human resource management division Software tools developed in the form of analytical tools in the form of applications consisting of SWOT Analysis, Competitive Profile Matrix, External and Internal environment analysis per business in the form of data analysis tables and diagrams that can illustrate weights, ratings and interpret the company's position and formulate strategies that are suitable for the company to apply. The development method carried out is the development model of Borg & Gall (2001) using waterfall grooves at the development stage. The results of this software development are called macro excel-based strategic planning applications) which are tested by including fictitious data on human resource management, IFA and EFA analysis, SWOT analysis, and Competitive Profile Matrix, and the result is a quadrant of strategies that formulate what strategies can be applied to the organization's resource management division.